Preventing work‐related stress among staff working in children's cancer Principal Treatment Centres in the UK: a brief survey of staff support systems and practices. (4th July 2016) - Beresford, B.; Gibson, F.; Bayliss, J.; Mukherjee, S.
Abstract : Growing evidence of the association between health professionals' well‐being and patient and organisational outcomes points to the need for effective staff support. This paper reports a brief survey of the UK's children's cancer Principal Treatment Centres (PTCs) regarding staff support systems and practices. A short on‐line questionnaire, administered in 2012–2013, collected information about the availability of staff support interventions which seek to prevent work‐related stress among different members of the multi‐disciplinary team (MDT). It was completed by a member of staff with, where required, assistance from colleagues. All PTCs ( n  = 19) participated. Debriefs following a patient death was the most frequently reported staff support practice. Support groups were infrequently mentioned. There was wide variability between PTCs, and between professional groups, regarding the number and type of interventions available. Doctors appear to be least likely to have access to support. A few Centres routinely addressed work‐related stress in wider staff management strategies. Two Centres had developed a bespoke intervention. Very few Centres were reported to actively raise awareness of support available from their hospital's Occupational Health department. A minority of PTCs had expert input regarding staff support from clinical psychology/liaison psychiatry.